Respuesta :
Answer:
d=11 So, the answer is B
Step-by-step explanation:
3(d+1)=4(d-2)
3d + 3 = 4d - 8
-3d +8 = -3d +8
_______________
0 + 11 = d + 0
11 = d
Equations are used to represent expressions of equal values
The value of 5(d - 2) for 3(d + 1) =4(d - 2) is (c) 45
The equation is given as:
[tex]3(d + 1) =4(d - 2)[/tex]
Open the brackets
[tex]3d + 3 =4d - 8[/tex]
Collect like terms
[tex]4d - 3d = 3 + 8[/tex]
[tex]d = 11[/tex]
Subtract 2 from both sides
[tex]d-2 = 11-2[/tex]
[tex]d-2 = 9[/tex]
Multiply both sides by 5
[tex]5(d-2) = 9 \times 5[/tex]
[tex]5(d-2) = 45[/tex]
Hence, the value of 5(d - 2) is (c) 45
Read more about equations at:
https://brainly.com/question/4916384